2019
DOI: 10.1007/978-981-13-2904-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Tigers at Critical Junctures: How South Korea, Taiwan and Singapore Survived Growth-Led Conflicts

Abstract: Early studies on the developmental state examined the characteristics of East Asian economies that, despite deviating from the conventional free-market model, succeeded in catching up with the developed world within a few decades after the Second World War. The general consensus is that developmental states are those that possessed: a centralized state structure; effective and autonomous bureaucracy; and a close and productive relationship between states and industries (Johnson 1982; Amsden 1989; Wade 1990; Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Furthermore, the analysis revealed that the presence of SOEs facilitated new industry entries in Vietnamese regions in the second period. This indicates that SOEs have the potential to be used as a developmental tool to accelerate structural change as has also been shown in other catch‐up contexts, such as China (Zhu et al ., 2019) or Singapore, where key industries were developed with the aid of SOEs a few decades ago (Kanchoochat, 2019). From a conceptual viewpoint, this result echoes the need to take multiple actors into account when analysing regional diversification and path creation (Hassink et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the analysis revealed that the presence of SOEs facilitated new industry entries in Vietnamese regions in the second period. This indicates that SOEs have the potential to be used as a developmental tool to accelerate structural change as has also been shown in other catch‐up contexts, such as China (Zhu et al ., 2019) or Singapore, where key industries were developed with the aid of SOEs a few decades ago (Kanchoochat, 2019). From a conceptual viewpoint, this result echoes the need to take multiple actors into account when analysing regional diversification and path creation (Hassink et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even among first-tier newly industrialising economies, divergent catch-up strategies significantly impact their development trajectories. For example, in South Korea, a chaebol-led growth strategy led the country to higher inequality and more contentious democratisation compared to Taiwan, which strongly supported small and medium enterprises (SMEs) and state-owned enterprises (Jeon 1995; Veerayooth 2017). Theoretically, this is a question about path dependence or how “the trajectory of change up to a certain point itself constrains the trajectory after that point” (Hay 2006: 64–65).…”
Section: Path Dependence and The Middle-income Trapmentioning
confidence: 99%
“…Consequently, there were not enough Members of Parliament to convene a new Parliament. This political tumult paved the way for the military coup on 22 May 2014 (see Veerayooth and Hewison 2017).…”
Section: Elected Governments After 1997mentioning
confidence: 99%